SeDOA - Servicestelle Diamond Open Access - Stäcker, Thomas; Apel, Jochen; Arning, Ursula; Burschel, Peter; Christof, Jürgen; Effinger, Maria; Elsner, Carsten; Finger, Juliane; Günther, Anne-Christine; Hagedoorn, Jan M; Jansky, Caroline; Kaiser, Michael; et al. (Zenodo, 2025)
The DFG-funded project ‘SeDOA’ aims to increase the efficiency of Diamond Open Access (DOA) publishing in Germany through better coordination and optimisation of decentralised services, provision of centralised information and innovation. - - The project is supported by a consortium of 15 institutions: - - - - Universitätsbibliothek der Freien Universität Berlin, - - Universitätsbibliothek der Humboldt-Universität zu Berlin, - - Universitätsbibliothek der Technische Universität Berlin, - - Medizinische Bibliothek, Charité - Universitätsmedizin Berlin, - - Universitätsbibliothek Bielefeld, - - Max-Weber-Stiftung Bonn, - - Universitätsbibliothek Braunschweig, - - Universitäts- und Landesbibliothek Darmstadt, - - Staats- und Universitätsbibliothek Hamburg, - - Universitätsbibliothek Heidelberg, - - FIZ Karlsruhe - Leibniz-Institut für Informationsinfrastruktur, - - ZBW - Leibniz-Informationszentrum Wirtschaft, - - Zentrale Fachbibliothek für Medizin Köln, - - Fachhochschule Potsdam, - - Herzog August Bibliothek Wolfenbüttel. - - - The AG Universitätsverlage is also directly involved. The project is led by the ULB Darmstadt, which is currently the spokesperson for the consortium, the University Library of the Humboldt University in Berlin and the Max Weber Foundation in Bonn. The partners will establish SeDOA as a single point of contact with an efficient communication infrastructure that involves all stakeholders (community of practice) in Germany. - - SeDOA has set itself the goal of promoting the Diamond Open Access concept in the community, making existing publication infrastructures more visible, contributing to their optimisation and developing its own complementary and innovative offerings. - - As the German Diamond Capacity Centre, it will be part of a European network and strengthen international cooperation. Planned are - - - - Needs analyses, - - Provision of information material, guidelines and guides, - - Organising workshops and training courses, - - Legal advice and, on a case-by-case basis, the preparation of legal opinions, - - Extensive national and international networking and communication work, - - Identification and consideration of disciplinary specialities via specialist associations, among others, - - Creating a better data basis by setting up a registry, - - Dynamisation of Diamond Open Access through innovative concepts and approaches in a SeDOA Innovation Lab (SIL).